Imaging and cancer of the cervix in low- and middle-income countries - Olpin, J. (Gynecol Oncol Rep, 2018)
Cervix cancer is the fourth most common cancer globally but the second most cancer in women in resource-limited countries. It has remained a clinically-staged neoplasm as per the International Federation of Gynecology and Obstetrics staging classification. As the imaging machines are becoming more available worldwide, the resource-stratified guidelines recommended the inclusion of imaging whenever possible to guide treatment planning. In this report, the utility of imaging in low- and middle-income countries for diagnosis and treatment of cancer of the cervix will be reviewed.